Tacrolimus pharmacology and nonclinical studies: from FK506 to protopic. - Bekersky, I; Lilja, H; Lawrence, I (2001)
Tacrolimus (FK506) is a calcineurin inhibitor with potent immunomodulating properties. It has been marketed worldwide since 1993-1994 for the rejection of liver and kidney transplants (Prograf). The pharmacologic properties of tacrolimus resulted in its development as an ointment for the treatment of atopic dermatitis. An outline of nonclinical pharmacology studies that provided a rationale for this development is presented. The key nonclinical toxicology-safety studies that supported clinical efficacy/safety trials are also discussed. Taken collectively, these studies contributed to the marketing approval of 0.03% and 0.1% tacrolimus ointment (Protopic) as a first in class treatment for atopic dermatitis.